Creating Conditions for Managing the Processes of Self-Organization of Ukrainian SocioEconomic Systems in the Decentralization Environment - Kovalenko, O.P. (Science and Innovation, 2024)
A concept for «meta-anthropological governance» of synchronous interaction of emergence, development, and functioning of socioeconomic organisms by the human being with philosophical worldview has been introduced. The economic, educational, organizational, and communication aspects of government as conditions for self-organization of community’s social environment have been discussed. A priority action plan for the community has been presented. Objectives and tasks have been formulated to develop and to implement the communication polylogue methodology for decision-making by the community and educational programs for fostering an archеtype philosophical worldview and stimulating the display of temporally hidden meta-anthropological capabilities of Ukrainians.